Penggunaan Media Audio Visual Al Arabiyah Baina Yadaik untuk Meningkatkan Keterampilan Kalam dan Istima’ Bagi Mahasiswa Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darul A’mal Lampung - Khabibul Khoiri; Joni Kawijaya (Institut Agama Islam Darul Fattah Lampung, 2025)
This study discusses the use of audio-visual media al arabiyah baina yadaik to improve the skills of kalam and istima' for students of the arabic language education study program at the islamic institute of darul a'mal lampung. The background of this study is the lack of active arabic language practice in everyday life, students experience difficulties in dialogue and understanding arabic conversations, which are overall due to the lack integration of digital-based media in the establised curriculum, resulting in low student abilities in kalam and istima' skills. the method used in this study is field research supported by observations, interviews, and documents of students arabic language learning activities. the result of this study indicate a significant increase in the skills of kalam and istima' possessed by students after the implementation of audio-visual media al arabiyah baina yadaik, beacuse this media provides direct practical experience in the form of audio and visuals sourced from native arabs. the findings of this study provide scientific contributions to islamic religious universities in learning kalam and istima' to continuously upgrade in using digital technology as a learning medium.